Impact of Problem-Based Learning on Students’ Mathematical Performance: A Quasi-Experimental Study - Siti Aminah; Pixyoriza; Siti Qomariyah (CV. SPDFHarmony, 2025)
Background: Many students still struggle to learn mathematics effectively, especially when lessons rely heavily on teacher explanations and lack real-world connection. To improve this, teaching strategies that involve students actively in the learning process are needed. One of them is the Problem-Based Learning (PBL) model, which helps students learn through solving meaningful problems. Aims: This study explores how the Problem-Based Learning model influences students’ understanding and performance in mathematics, focusing on the topic of linear equations in two variables for Grade VIII students. Methods: A quasi-experimental design was applied, involving two student groups: one group was taught using the PBL model, while the other used traditional instruction. Students were given problem-solving tests before and after the learning activities. These tests were used to see how their skills developed during the learning process. Finding: Students who took part in the learning process using the PBL method showed better understanding and stronger problem-solving abilities than those in the conventional group. The approach encouraged them to think more deeply, participate actively, and relate mathematics to everyday situations. Significance: This research highlights that PBL can be a useful method for improving students’ learning results in mathematics. Teachers are encouraged to consider using this model in their classes to make learning more meaningful and effective.